PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN CA GADING SERPONG - Vincent Vincent; Steven Nathanael; Timotius Handi Winata (CV. Aksara Global Akademia, 2023)
This research can be conducted on the number of customers who visit Angkringan CA Gading Serpong by using various kinds of social media so that this form of purchase decision becomes evidence from customers who are interested in buying Nasi Kucing products. Likewise, it is important for Angkringan CA Gading Serpong to use digital marketing, because social media has a strong influence on promoting the product. Analysis can be carried out using quantitative research methods, because this research will discuss the 4P strategy, namely Product, Price, Place and Promotion which will be part of the four main keys to making a marketing strategy for Nasi Kucing which will be sold by Angkringan CA Gading Serpong. In terms of target customers, the average consumer who eats at this angkringan is students because access to this angkringan is not far from the university. This study has twenty kinds of indicators consisting of Product Quality, Product Design, Product Brand, Product Variants, Affordable Prices, Sales Competitiveness, Price Compatibility, Strategic Location, Affordable and Convenient, Order System more regularly, Media Promotion, Communication, Product Introduction , Advertising intensity through Food Blogger, so that the stability of a product is proven to satisfy customers and become loyal, a questionnaire needs to be made with a target of reaching 110 respondents who are customers of Angkringan CA Gading Serpong. This is a form of participation in filling out the questionnaire.